(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The research aims to study the impact of organizational pride on business continuity in private colleges and universities in Baghdad, and the research problem is summarized in the main question (were academic leaders able to employ organizational pride to enhance business continuity? The research applied in the private education sector, and private universities and colleges in the city of Baghdad were the field for this. The research was selection of the research community based on the founding year of the college or university as more than ten years have passed since its founding. The research sample consists of (177) individuals, from deans of the colleges and their assistants as well as the heads of scientific and administrative departments. The researcher adopted the descriptive analytical approach. The questionnaire used as a main tool for collecting data for the applied side. After evaluating and testing the validity and reliability of the research measurement tools. The data analyzed and hypotheses tested using the appropriate statistical tools using the statistical program (SPSS) (AMOS) to analyze the data. The results showed that there is a significant effect of organizational pride in Business continuity.